2005
DOI: 10.1111/j.1365-2249.2005.02889.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms dependent on tryptophan catabolism regulate immune responses in primary Sjögren's syndrome

Abstract: SummaryTo investigate the possible role of tryptophan metabolism in immune regulation of primary Sjögren's syndrome (pSS) the serum concentrations of tryptophan and its metabolite kynurenine were measured by reverse-phase high-performance liquid chromatography (HPLC) in 103 patients with pSS, 56 patients with sicca symptoms and 309 healthy blood donors. The kynurenine per tryptophan ratio (kyn/trp), which reflects the activity of the indoleamine-pyrrole 2,3-dioxygenase (IDO) enzyme involved in tryptophan catab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 22 publications
5
57
2
Order By: Relevance
“…On the other hand, a higher percentage of IDOexpressing APCs was observed supported in pSS than in healthy controls [31]. Increased KYN concentration and KYN/TRP ratio, which reflects the activity of IDO, were also measured in the peripheral blood of pSS patients [32]. In our study, we found that the frequency of IDO-expressing APCs, as well as intracellular IDO content in T cells, was higher in pSS than in controls.…”
Section: Idosupporting
confidence: 54%
“…On the other hand, a higher percentage of IDOexpressing APCs was observed supported in pSS than in healthy controls [31]. Increased KYN concentration and KYN/TRP ratio, which reflects the activity of IDO, were also measured in the peripheral blood of pSS patients [32]. In our study, we found that the frequency of IDO-expressing APCs, as well as intracellular IDO content in T cells, was higher in pSS than in controls.…”
Section: Idosupporting
confidence: 54%
“…DC, to express IDO, which can limit T cell responses [24]. Moreover, IDO has been found to be elevated in autoimmune diseases with a female preponderance, for example systemic lupus erythematosus [25] and Sjögren's syndrome [26]. On the other hand, either early atherosclerosis or precociously increased IMT has been found in both these autoimmune diseases [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…have been shown to overexpress in a variety of cancers, including lung cancer. However, autoantibodies immunoreactive to these antigens are rarely reported in cancer patients but associated with some inflammatory or metabolic diseases (34,35), implicating that tumor antigen-mediated immunosuppression may occur in tumor malignancy. Consistent with previous studies to detect CML28 (36) and ENO1 (14) autoantibodies in chronic myelogenous leukemia and lung patients, respectively, our data obtained from Western blotting analyses also show that only a small percentage (7.4%) of the cancer patients, including patient CA926, develop high titer of antibodies against ENO1.…”
Section: Discussionmentioning
confidence: 99%